Regulation of the wind power production: contribution of the electric vehicles and other energy storage systems - Mateus, C. B. (2013)
The increase in penetration of variable renewable energy sources (RES) introduced additional difficulties regarding the management of the Portuguese Power System. This is mainly due to the high temporal variability and low controllability, characteristics of these kinds of sources. There is a real need to reduce the impact of non-dispatchable RES sources; maximizing their penetration and minimizing curtailment. This is especially true for the wind power and run-of-the-river hudro (ROR); as it appears beneficial to combine their variable production with added capacity of energy storage and demand side management; thereby increasing the flexibility of the power system as a whole. This paper aims to assess the excess wind generation (and other non-dispatchable sources); this for periods of production's excess in a 2020 timeframe, and assuming different weather scenarios. The adjustment of wind power generation (WPG) profile to the load prfile is also addressed; the result is computed in the form of the value of the energy temporally deferred, using Pumped Hydro Storage (PHS) power plants as well as electric Vehicles (EVs)